Plurilinguisme et construction des savoirs disciplinaires dans l’enseignement universitaire - Müller, Gabriele M.; Pantet, Jeanne (Travaux neuchâtelois de linguistique, 2008)
In which way is multilingualism a resource for knowledge construction? By analysing examples from interactions in a bilingual university lecture, this article aims to show a set of first research results concerning this issue.